2021
DOI: 10.1007/s42452-021-04224-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for the steady nanofluid boundary layer flow over a moving plate with suction and heat generation

Abstract: In the study, the steady, laminar, incompressible, convective flow of a viscous fluid over a moving plate is investigated theoretically by adopting different types of nanoparticles. Radiation, internal heat generation and viscous dissipation effects are considered in the energy modeled equation. The governing flow equations for the momentum and temperature are reduced to dimensionless form via similarity transformations. The solutions to the resultant equations alongside with the transformed boundary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The recent developments in this regard can be assess in References. [13][14][15] The fluid with nanosized particles is termed as nanofluid. Owning to importance of nanofluids various authors reported their finds like Rahman et al 16 discussed the suspended nanoparticles in the fluid flow past a porous exponentially stretching/shrinking by using the Buongiorno's model.…”
Section: Introductionmentioning
confidence: 99%
“…The recent developments in this regard can be assess in References. [13][14][15] The fluid with nanosized particles is termed as nanofluid. Owning to importance of nanofluids various authors reported their finds like Rahman et al 16 discussed the suspended nanoparticles in the fluid flow past a porous exponentially stretching/shrinking by using the Buongiorno's model.…”
Section: Introductionmentioning
confidence: 99%
“…A wide-range of possible applications has been initiated for the use of nanofluids. Choi remained the first to research updraft conductivity development in nanofluids [1][2][3][4][5][6][7][8][9][10][11][12]. Nanofluids, bio and pharmacological nanofluids, remedial nanofluids, environmental nanofluids, and other heat transfer fluids are categorized according to their applications.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of applications of nanofluids in thermal systems led researchers to study nanofluid flow and heat transfer processes under different thermophysical conditions and geometries. Ferdows et al [10] studied the behaviour of viscous nanofluid in the presence of internal heat generation and suction by considering copper and aluminium nanoparticles. The governing equations are solved numerically after utilizing the similarity transformations to see the behaviour of key parameters of flow and heat transfer.…”
Section: Introductionmentioning
confidence: 99%